Immunologic Clearance of a BK Virus-associated Metastatic Renal Allograft Carcinoma. Issue 2 (February 2021) - Meier, Raphael P.H.; Muller, Yannick D.; Dietrich, Pierre-Yves; Tille, Jean-Christophe; Nikolaev, Sergey; Sartori, Ambra; Labidi-Galy, Intidhar; Ernandez, Thomas; Kaur, Amandeep; Hirsch, Hans H.; McKee, Thomas A.; Toso, Christian; et al.
Abstract : Background: Metastatic carcinoma of a renal allograft is a rare but life threatening event with a difficult clinical management. Recent reports suggested a potential role of BK polyomavirus (BKPyV) in the development of urologic tract malignancies in kidney transplant recipients. Methods: We investigated a kidney-pancreas female recipient with an history of BKPyV nephritis who developed a rapidly progressive and widely metastatic donor-derived renal carcinoma 9 years after transplantation. Results: Histology and fluorescence in situ hybridization analysis revealed a donor-derived (XY tumor cells) collecting (Bellini) duct carcinoma. The presence of BKPyV oncogenic large tumor antigen was identified in large amount within the kidney tumor and the bowel metastases. Whole genome sequencing of the tumor confirmed multiple genome BKPyV integrations. The transplanted kidney was removed, immunosuppression was withdrawn, and recombinant interleukin-2 (IL-2) was administered for 3 months, inducing a complete tumor clearance, with no evidence of disease at 6-year follow-up. The immunological profiling during IL-2 therapy revealed the presence of donor-specific T cells and expanded cytokine-producing bright natural killer cells but no donor-specific antibodies. Finally, we found persistently elevated anti-BK virus IgG titers and a specific anti-BKPyV T cell response. Conclusions: This investigation showed evidence for the potential oncogenic role of BKPyV in collecting duct carcinoma in renal allografts and demonstrated that immunosuppression withdrawal and IL-2 therapy can lead to an efficient antitumor cellular mediated rejection possibly via 3 distinct mechanisms including (1) host-versus-graft, (2) host-versus-tumor, and (3) anti-BKPyV responses. Abstract : Supplemental Digital Content is available in the text.